GENDER DALAM KELUARGA BERENCANA (STUDI KASUS PARTISIPASI SUAMI DALAM MELAKUKAN KONTRASEPSI DI KELURAHAN MACANRE KECAMATAN LILIRILAU KABUPATEN SOPPENG) - Nadyah; Afiif, Ahmad (JURNAL SIPAKALEBBI, 2020)
Family planning (KB) is one of the government programs to reach a prosperous family by organizing or planning a pregnancy. KB is a means for families to plan the creation of an ideal family, a small, happy and prosperous family. Until now, family planning program in Indonesia has not paid attention to gender equality because in general the target of family planning services is dominated by women. Because of this condition, the purpose of this study is to describe the participation of husbands in the family planning program in this village of Macanre and know what affects the participation of husbands in the family planning program. This type of study uses a descriptive method whereby data collection techniques are conducted with observations, documentation, and a deep interview to the community using sampling techniques with purposive sampling methods. The results were obtained indicating that in contraceptives the involvement of husbands in the village of Macanre very low. This condition is because it is based on the public belief that all responsibility in reproductive health is borne by women (wives), roles and reproductive functions related to the female body (wife) is the responsibility of women without human involvement (husband). People who are still closed and the taboo reproductive health problems are also a factor that causes the low role of husband to the reproductive health of the wife. Based on this, the need for guidance and education on reproductive health to the public is essential to increase knowledge and participation in family planning.